SOSISALISASI PROGRAM KIE BAGI PASANGAN USIA SUBUR DI DPPKBP3A KABUPATEN SUMEDANG - Salisa, Ukhtiana (JRPA - Journal of Regional Public Administration, 2025)
This study discusses the implementation of e-government in population services at the Population and Civil Registration Office of Sumedang Regency through the use of the Tahu Sumedang application. The study aims to understand the extent to which the application of information technology can improve the efficiency of public services and identify inhibiting factors and efforts made in the digitalization process. The research method used is descriptive qualitative with a case study approach. The results of the study indicate that although the Tahu Sumedang application provides easy access to administrative services such as making ID cards, birth certificates, and family cards, its implementation is still constrained by the lack of socialization to the community, limited competent workers, and inefficient verification flows. The competency gap between ASN and non-ASN employees also affects the effectiveness of services. To overcome this, the Disdukcapil has conducted training and system adjustments, although the results have not been optimal. This study recommends increasing human resource capacity and optimizing digital management as strategic steps towards effective and efficient public services.